Electrochemical Reactive Separation: Asymmetric Redox‐Polymer Interfaces for Electrochemical Reactive Separations: Synergistic Capture and Conversion of Arsenic (Adv. Mater. 6/2020). Issue 6 (11th February 2020) - Kim, Kwiyong; Cotty, Stephen; Elbert, Johannes; Chen, Raylin; Hou, Chia‐Hung; Su, Xiao
Abstract : Redox‐active polymers offer a powerful platform for integrating separation and reactions. In article number 1906877, Xiao Su and co‐workers report an asymmetric electrochemical system consisting of a metallopolymer and an organic radical polymer for the synergistic capture and conversion of arsenic. The proposed strategy highlights new opportunities for redox‐active materials in electrochemical process intensification, water purification, and environmental remediation.